Event as a Text Category and Most Typical Peculiarities of Its Expression in Language - Znamenskaitė, Rozita (Kalbotyra, 2002)
This article examines about events as a category of the text and their expression in Lithuanian. Event is considered to be a special category, different from other event-like text categories (such as incident, situation, process, circumstance, state of affairs, fact and so on). This article describes some special signs of event which help us to recognise event in the text. Event can be described in a small text (consisting of one or two utterances) as well as in a longer text. It all depends on the importance of the event.